Parceling as a Method of Expressive Syntax in the System of Oksana Pakhlovska’s Individual Style (Linguostylistic Studies, 2015)
The article is dedicated to the nature of parceling (fragmentary sentences) in the poetic, prosaic texts and essays of Ukrainian and Italian poet, writer and literary critic Oksana Pakhlovska. Considered here are the main approaches to the definition of the term «parceling» in linguistics and also its role as the method of expressive syntax. The article deals with different types of parceling: parceling of subject, predicate, object, attribute, adverbial modifier, coordinate clause, subordinate clause, composite asyndetic clause and paragraph parceling. Analyzed here are those types of fragmentary sentences, which are most frequently used in Oksana Pakhlovska’s poems, short stories and essays. The main functions of parceling in the author’s individual style are determined in this article. Among them are: descriptive, meaning-making, emotive, logical, the function of concretization of the plot, the rhythm-making function, the function of «hidden» irony and some others. Key words: individual style, expressive syntax, parceling, fragmentary sentence, construction, function. References